2009
DOI: 10.1130/l30.1
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of the lithospheric mantle in an extensional setting: Insights from ophiolitic peridotites

Abstract: We present a model of mantle lithosphere evolution in an extensional setting based on the structure and petrology of the Alpine-Apennine ophiolitic peridotites from the Jurassic Ligurian Tethys Ocean. Continental extension and rifting in the Ligurian domain were induced by far-fi eld tectonic forces and were characterized by the interplay of tectonic and magmatic processes. Extension and thinning of the lithosphere induced adiabatic upwelling and decompression melting of the asthenosphere. Mid-ocean-ridge basa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 27 publications
(44 reference statements)
2
22
0
Order By: Relevance
“…The low content of Al 2 O 3 (av. 0.96%) in the study area indicates depleted peridotites which generally formed at more distal (internal, oceanic) settings of the basin, represent refractory residua after asthenosphere partial melting and MORB extraction and to be similar to modern abyssal peridotites (Piccardo et al, 2009). The occurrence of depleted mantle is associated with fast spreading ridges, which favour the formation of most refractory peridotites (Godard et al, 2008).…”
Section: Geochemistrymentioning
confidence: 75%
See 1 more Smart Citation
“…The low content of Al 2 O 3 (av. 0.96%) in the study area indicates depleted peridotites which generally formed at more distal (internal, oceanic) settings of the basin, represent refractory residua after asthenosphere partial melting and MORB extraction and to be similar to modern abyssal peridotites (Piccardo et al, 2009). The occurrence of depleted mantle is associated with fast spreading ridges, which favour the formation of most refractory peridotites (Godard et al, 2008).…”
Section: Geochemistrymentioning
confidence: 75%
“…29.62%) showing relevance with Alpine peridotites. The Alpine peridotites are characterized by strong compositional heterogeneity, because they face multiple processes including partial melting and melt extraction (Piccardo et al, 2009).…”
Section: Geochemistrymentioning
confidence: 99%
“…In their scheme, the HT LP plagioclase peridotites have undergone a complex history of regional-scale melt infiltration and melt-rock reaction that has erased most of the ancient (lithospheric) history that is otherwise preserved in LT LP spinel peridotites. This process, coupled with thermomechanical erosion by upwelling asthenosphere, would result in the rejuvenation ('asthenospherization') of subcontinental lithosphere beneath rifted margins (see also, for the Alps, Mü ntener and Piccardo, 2003;Mü ntener et al, 2004Mü ntener et al, , 2005Piccardo and Guarnieri, 2010;Piccardo et al, 2004bPiccardo et al, , 2009Ranalli et al, 2007;. Several studies have reported geochemical analyses of LP orogenic peridotites from the Western Alps.…”
Section: Western Alpsmentioning
confidence: 95%
“…In contrast with mantle xenoliths, the massif and abyssal peridotites do not generally represent lithospheric mantle that has been stabilized for a sufficient period of time to be traversed by intraplate magmatism. Some orogenic peridotites probably include relatively old lithospheric mantle components (see Section 3.4.5.2.1), but they were generally strongly 'asthenospherized' -both thermally and chemically -before their exhumation (Le Roux et al, 2007;Lenoir et al, 2001;Mü ntener et al, 2005Mü ntener et al, , 2010Piccardo et al, 2007aPiccardo et al, , 2009.…”
Section: Metasomatized Orogenic Peridotitesmentioning
confidence: 96%
See 1 more Smart Citation